2017
DOI: 10.3389/fmicb.2017.00956
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Nitrate-Mediated Control of the Oil Field Sulfur Cycle Depends on the Toluene Content of the Oil

Abstract: The injection of nitrate is one of the most commonly used technologies to impact the sulfur cycle in subsurface oil fields. Nitrate injection enhances the activity of nitrate-reducing bacteria, which produce nitrite inhibiting sulfate-reducing bacteria (SRB). Subsequent reduction of nitrate to di-nitrogen (N2) alleviates the inhibition of SRB by nitrite. It has been shown for the Medicine Hat Glauconitic C (MHGC) field, that alkylbenzenes especially toluene are important electron donors for the reduction of ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 36 publications
(75 reference statements)
2
21
0
Order By: Relevance
“…Experiments with batch cultures and bioreactors in which heavy MHGC oil was the only available electron donor indicated absence of PRB capable of coupling the reduction of perchlorate to the oxidation of oil components ( Figures 3 , 5 and Supplementary Figure S1 ). Nitrate was reduced to nitrite and dinitrogen under these conditions, which resulted in removal of alkylbenzenes from the oil ( Supplementary Figure S1 ), as found previously ( Lambo et al, 2008 ; Agrawal et al, 2012 ; Suri et al, 2017 ). Because perchlorate was not reduced it was inert, i.e., no high-potential electron transport pathways were operating, and sulfide production was observed both in enrichment cultures and bioreactors containing sulfate and perchlorate.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Experiments with batch cultures and bioreactors in which heavy MHGC oil was the only available electron donor indicated absence of PRB capable of coupling the reduction of perchlorate to the oxidation of oil components ( Figures 3 , 5 and Supplementary Figure S1 ). Nitrate was reduced to nitrite and dinitrogen under these conditions, which resulted in removal of alkylbenzenes from the oil ( Supplementary Figure S1 ), as found previously ( Lambo et al, 2008 ; Agrawal et al, 2012 ; Suri et al, 2017 ). Because perchlorate was not reduced it was inert, i.e., no high-potential electron transport pathways were operating, and sulfide production was observed both in enrichment cultures and bioreactors containing sulfate and perchlorate.…”
Section: Discussionsupporting
confidence: 55%
“…Studies on the control of sulfide production with nitrate in heavy oil-containing bioreactor columns as well as in the field have shown that alkylbenzenes (toluene, ethylbenzene, and m - and p -xylene) were utilized as electron donors for nitrate reduction ( Lambo et al, 2008 ; Agrawal et al, 2012 ; Suri et al, 2017 ), whereas alkylbenzenes and alkanes were used as electron donors for sulfate reduction ( Agrawal et al, 2012 ). Acetate accumulated transiently as an intermediate in the metabolism of these oil components under sulfate-reducing, but not under nitrate-reducing conditions ( Callbeck et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…To prepare the inoculum for this study, produced water was obtained from five production wells (PW; 4-PW, 7-PW, 18-PW, 32-PW, 33-PW; Figure S1 ) in the Medicine Hat Glauconitic C (MHGC) field (Voordouw et al, 2009 ). Although this oilfield has been used as a study site for nitrate treatment of souring for 10 years (Suri et al, 2017 ), previous investigations of this oilfield have reported chemical and functional evidence of nitrate-free “zones” harboring active methanogenic archaea (Agrawal et al, 2012 ), from which all PW samples were collected for this study. Berdugo-Clavijo and Gieg ( 2014 ) also demonstrated that methanogenic crude oil biodegradation could be established from these produced waters.…”
Section: Methodsmentioning
confidence: 99%
“…Nitrate has been used as a biological treatment in oil reservoir systems since the 1990s ( Coates et al, 1993 ; Hubert et al, 2003 ; Arensdorf et al, 2009 ; Gieg et al, 2011 ). This treatment has direct and indirect effects on sulfate reduction but is not always predictable ( Hubert and Voordouw, 2007 ; Voordouw et al, 2009 ; Gieg et al, 2011 ; Carlson et al, 2015a ; An et al, 2017 ; Okpala et al, 2017 ; Suri et al, 2017 ; Engelbrektson et al, 2018 ). Nitrate has multiple mechanisms of action to control sulfate reduction.…”
Section: Introductionmentioning
confidence: 99%